Analisa Pengendalian Internal Terhadap Pembiayaan Mudharabah Studi Kasus Pembiayaan Mudharabah Bank Syariah Mandiri Cabang Kebon Jeruk - Alfiya, Evi; Heykal, Mohammad (Binus Business Review, 2014)
The purpose of this research is to determine the financing procedure of PT. Bank Syariah Mandiri of Kebon Jeruk Branch runs in accordance with the procedures and objectives of the company that are set and to determine the appropriateness of accounting calculation of mudharaba and journal entries based on mudharaba PSAK 105, as well as internal control procedures to determine the portion of financing based on the COSO standards. The method used is a literature study to obtain basic theory that is applied to the evaluation of the problem and also a field study with observation, interviews, and a collection of documents administrative staff financing, accounts officer, back office officer as the staff SDI. These results indicate that the procedure is carried out on the financing of PT. Bank Syariah Mandiri has been in accordance with the practice and application of recording and journalizing of financing applied by PT. Bank Syariah Mandiri of Kebon Jeruk Branch not in accordance with PSAK 105, because there are still some things that have not been applied correctly. The authors findings related to inadequate segregation of duties, the authors recommend that companies look for new employees for the position of legal officer, staff SDI and IT coordinator. Overall, the authors concluded that the company has been designing and implementing five components of internal control over financing.